Debtor's Responsibility For Land Certificate Owned By Third Party As Substitute Collateral In Bank - Muhammad Abdul Hakim Aliy Ainun Musyarif; Merline Eva Lyanthi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
The purpose of writing this journal is to examine and analyze the responsibility of debtors toward the owners of land title certificates that are used as replacement collateral in bank credit agreements. The central problem discussed in this paper is the extent to which debtors are legally accountable to third-party landowners whose property has been pledged as collateral. This issue is crucial because, in practice, many debtors lack sufficient assets to secure loans and therefore rely on third parties who voluntarily provide their land ownership certificates to support the debtor’s credit application. In conducting this research, the method employed is a normative juridical approach, which relies on the study of positive law applicable in Indonesia. The analysis is based on primary sources such as the 1945 Constitution of the Republic of Indonesia, the Civil Code, relevant statutory regulations, and specifically the Mortgage Law (Undang-Undang Hak Tanggungan). In addition, the research is supported by secondary sources, including expert legal opinions, academic literature, and jurisprudence, which provide interpretation and context for the application of these legal provisions. This study places emphasis on the importance of legal protection for third-party owners who provide collateral. The findings conclude that debtors are obligated to assume full responsibility for third-party property pledged as collateral. If the debtor fails to meet contractual obligations, the debtor may face sanctions or penalties, as such violations constitute a breach of contract under Indonesian law.